Stimulating Early Childhood Digital Literacy Through the Innovative Kiddyfun Platform - Putri, Novi Eka; Iriyanto, Tomas; Anisa, Nur (Universitas Pendidikan Ganesha, 2024)
The globalization era significantly impacts daily behavior, including the field of education. This highlights the necessity for individuals to continuously adapt to avoid being left behind by rapid advancements. However, in practice, the utilization of digital literacy remains suboptimal, as teachers often rely solely on books as learning resources, which can lead to student disengagement when faced with lengthy texts. This study aims to produce the Kiddyfun platform, designed to be effective, efficient, and engaging in stimulating digital literacy skills among children aged 4–6 years. The study subjects included two material expert validators, two media expert validators, four teacher users, 40 children aged 4–5 years, and 40 children aged 5–6 years. The research employed a development method based on the ADDIE model. Data collection techniques involved observation sheets and questionnaires, analyzed using quantitative descriptive methods. The results showed that the media validity test scored 89% (highly feasible), the material validity test scored 94% (highly feasible), the user test scored 97% (highly feasible), the small group test scored 100% (highly feasible), and the large group test scored 96% (highly feasible). Based on these results, it can be concluded that the innovation of Kiddyfun platform is highly feasible and engaging. The implication of this media development is its potential to enrich digital learning resources to stimulate literacy skills in children aged 4–6 years.